Implementasi Nilai Keadilan Ekonomi Syariah Melalui Edukasi Anti Riba dan Gerakan Menabung dalam Membangun Mentalitas Anak : Studi Kasus di Dusun II Sei Parit, Kecamatan Sei Rampah, Kabupaten Serdang Bedagai - Fara Natasya Hamzah Lubis; Nur Rahma Amini (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program was held at SD Negeri 102028 Dusun II Sei Parit, Sei Rampah District, Serdang Bedagai Regency, with a focus on applying the principles of sharia economic justice. This goal is achieved through education about the prohibition of usury and savings initiatives from an early age. This activity was motivated by the lack of Islamic financial literacy among children, especially related to the risk of usury and the urgency of frugal behavior and financial responsibility. The method chosen is a participatory-educational approach, which includes socialization, simulation and habituation, prioritizing the active involvement of students. The activity is divided into two main phases, namely usury education and saving education, utilizing animated films, educational games and picture stories. The impact of this service shows an increase in students' insight into the concept of riba, discipline in frugality, and the growth of awareness to manage money wisely according to Islamic guidance. Children are now beginning to understand that money is a mandate that must be used correctly and halal. In addition, this program also encourages the formation of the character of responsibility, trust and justice in the participants. Therefore, this program makes a significant contribution in building a children's mentality based on the principles of sharia economic justice and is worthy of being used as a prototype of Islamic financial education at the elementary school level.